2016
DOI: 10.1126/science.aad9682
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling after civil conflict increases social capital but decreases individual well-being

Abstract: Civil wars divide nations along social, economic, and political cleavages, often pitting one neighbor against another. To restore social cohesion, many countries undertake truth and reconciliation efforts. We examined the consequences of one such effort in Sierra Leone, designed and implemented by a Sierra Leonean nongovernmental organization called Fambul Tok. As a part of this effort, community-level forums are set up in which victims detail war atrocities, and perpetrators confess to war crimes. We used ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 82 publications
3
62
0
6
Order By: Relevance
“…Critiques have suggested that the proceedings have increased levels of depression and Post‐Traumatic Stress Disorder among participants (Brounéus, ), and that participants were dissatisfied with the process (Pozen, Neugebauer, & Ntaganira, ). However, the presence of psychological stress is consistent with the findings of Cilliers, Dube and Siddiqi () who suggest that post‐conflict reconciliation may rebuild social capital while decreasing individual well‐being. Similarly, Doughty (2015) argues that, “divisive dynamics in gacaca do not merely reflect institutional failures but, rather, reflect the inherent violence of social repair.”…”
Section: Critiques Of Gacacasupporting
confidence: 88%
“…Critiques have suggested that the proceedings have increased levels of depression and Post‐Traumatic Stress Disorder among participants (Brounéus, ), and that participants were dissatisfied with the process (Pozen, Neugebauer, & Ntaganira, ). However, the presence of psychological stress is consistent with the findings of Cilliers, Dube and Siddiqi () who suggest that post‐conflict reconciliation may rebuild social capital while decreasing individual well‐being. Similarly, Doughty (2015) argues that, “divisive dynamics in gacaca do not merely reflect institutional failures but, rather, reflect the inherent violence of social repair.”…”
Section: Critiques Of Gacacasupporting
confidence: 88%
“…Cilliers et al . () show, also in Sierra Leone, that reconciliation increases self‐reported measures of forgiveness and trust towards ex‐combatants among villagers. In the Ugandan context, we do not find evidence of mistrust or preference‐based discrimination in behavioural experiments, suggesting that these factors are unlikely to drive the employment gap observed among former soldiers.…”
mentioning
confidence: 87%
“…In Sierra Leone, a survey of ex-combatants documents that increased exposure to violence is associated with reports of a lower community acceptance (Humphreys and Weinstein, 2007). Cilliers et al (2016) show, also in Sierra Leone, that reconciliation increases self-reported measures of forgiveness and trust towards ex-combatants among villagers. In the Ugandan context, we do not find evidence of mistrust or preference-based discrimination in behavioural experiments, suggesting that these factors are unlikely to drive the employment gap observed among former soldiers.…”
mentioning
confidence: 97%
“…Enduring resentment and feelings of revenge can only generate lasting unhappiness among affected parties. Promoting reconciliation at the national level (e.g., through Truth Commissions) can create the necessary conditions for a change in people's attitudes, but these collective efforts may have drawbacks (Cilliers, Dube, & Siddiqi, 2016;Twose, & Mahoney, 2015;Kpanake & Mullet, 2011). As a result, examining how former opponents in countries which have experienced bloody internal conflicts are able to personally forgive and to feel forgiven is not a futile exercise (Cárdenas, Páez, Arnoso, & Rimé, 2017;Gibson, 2007, López López, León Rincón, Pineda Marín, & Mullet, 2018.…”
Section: Forgiving Perpetrators Of Violencementioning
confidence: 99%